2004
DOI: 10.1080/0968776042000259573
|View full text |Cite
|
Sign up to set email alerts
|

Don't write, just mark: the validity of assessing student ability via their computerized peer-marking of an essay rather than their creation of an essay

Abstract: This paper reports on a case study that evaluates the validity of assessing students via a computerized peer-marking process, rather than on their production of an essay in a particular subject area. The study assesses the higher-order skills shown by a student in marking and providing consistent feedback on an essay. In order to evaluate the suitability of this method of assessment in judging a student's ability, their results in performing this peer-marking process are correlated against their results in a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…The results of the research demonstrated a changing process of the students' behaviours similar to the previous studies such as (Davies, 2004;Hamalainen, Hyyrynen, Ikonen, & Porras, 2011;Moore & Teather, 2013;Double, McGrane, & Hopfenbeck, 2020) through the peer-learning activities. The students developed the style of thoughts through the exercise.…”
Section: Discussionsupporting
confidence: 80%
“…The results of the research demonstrated a changing process of the students' behaviours similar to the previous studies such as (Davies, 2004;Hamalainen, Hyyrynen, Ikonen, & Porras, 2011;Moore & Teather, 2013;Double, McGrane, & Hopfenbeck, 2020) through the peer-learning activities. The students developed the style of thoughts through the exercise.…”
Section: Discussionsupporting
confidence: 80%
“…The study highlights the writing errors of the students at B2 level, and the type of text is essay. Davies (2004) reports that essays are regarded as a mechanism for evaluating a student's subjective competencies. Therefore, in this study, essay type was employed for revealing the students' competencies in writing by evaluating their errors, and B2 level was taken as a reference.…”
Section: Introductionmentioning
confidence: 99%
“…Davies (2004) however suggested the use of peer review process in assessment as a tool for the improvement of learning and discovering plagiarism. Carroll (2007, p. 47) suggested that learning can be assessed by requiring an outline or annotated list of sources and drafts instead of an essay in some instances.…”
Section: Using Assessment To Deter Plagiarismmentioning
confidence: 99%